Korean Shamanistic rituals - Lee, Jung Young ([Place of publication not identified] : [De Gruyter] ; The Hague : Mouton Publishers, 2018)
The series Religion and Society (RS) contributes to the exploration of religions as social systems- both in Western and non-Western societies; in particular, it examines religions in their differentiation from, and intersection with, other cultural systems, such as art, economy, law and politics. Due attention is given to paradigmatic case or comparative studies that exhibit a clear theoretical orientation with the empirical and historical data of religion and such aspects of religion as ritual, the religious imagination, constructions of tradition, iconography, or media. In addition, the form.
Intro; Preface; Contents; List of Plates; The Origin and Formation of Korean Shamanism; Chaesu gut: The Fundamental Ritual of Korean Shamanism; Shamanistic Songs, Oracles and Prayers; Ritualistic Instruments; Seasonal Rituals; Temporary Rituals; Rituals for the Dead; Communal Rituals; Divination and Shamanistic Rituals; Shamanistic Rituals and Traditional Homes; Shamanism and Sexual Repression; APPENDIX I Charm Symbols; Appendix II Plates; Bibliography on Korean Shamanism; Index
Includes bibliographical references and index.
Description based upon print version of record.
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Shamanism -- Korea; Shamanism -- Korea (South); BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism.; RELIGION / Comparative Religion; Electronic books